Comparison between ERA Interim/ECMWF, CFSR, NCEP/NCAR reanalysis, and observational datasets over the eastern part of the Brazilian Northeast Region - de Lima, Jessé Américo Gomes; Alcântara, Clênia Rodrigues (Theoretical and applied climatology, 2019)
Many studies have tried to determine the more accurate gridded datasets for a specific region of the world. This subject is complex given all available datasets, modeling approaches, and spatial and temporal resolutions. This study aimed to compare the results of reanalysis derived from climate indexes over eastern part of the Brazilian Northeast Region for temperature extremes and annual accumulated precipitation. Indexes from the Expert Team on Climate Change Detection and Indices were employed to compare the Climate Forecast System Reanalysis, ERA Interim, and National Centers for Environmental Prediction/National Center for Atmospheric Research gridded data with data of 36 stations from the Instituto Brasileiro de Meteorologia network. The results showed that the ERA Interim reanalysis had the lowest root mean square errors when compared to observe accumulated precipitation data and temperature indexes. In addition, this study provided an overview of the geographical characteristics of the error variation for each station studied with the aim of supporting future works.